Childhood Trauma Associations With the Interpersonal Psychological Theory of Suicide and Social Cognitive Biases in Psychotic Disorders. Issue 6 (29th June 2022) - Chalker, Samantha A.; Parrish, Emma M.; Cano, Mayra; Kelsven, Skylar; Moore, Raeanne C.; Granholm, Eric; Pinkham, Amy; Harvey, Philip D.; Depp, Colin A.
Abstract: Childhood trauma (CT) is associated with suicidal ideation and behaviors (SI/SB) in people with psychosis. The interpersonal psychological theory of suicide (IPTS) suggests that there are four factors that increase suicide risk: thwarted belongingness, perceived burdensomeness, acquired capacity for suicide, and hopelessness. The IPTS constructs and social cognitive biases are associated with SI/SB in psychotic disorders. However, the role of CT in IPTS constructs and social cognitive biases has not been examined in psychosis. In an outpatient community sample of persons with psychotic disorders ( N = 96) assessed with the Childhood Trauma Questionnaire, the aims of this study were to a) evaluate rates of CT in this sample, b) determine the relationship between CT types and lifetime SI/SB, and c) explore the relationship between CT types, IPTS constructs, and social cognitive biases. All participants reported experiencing CT. Emotional abuse was associated with greater SI severity and higher rates of lifetime suicide attempts, as well as with greater perceived burdensomeness and more severe negative social cognitive biases. Other CT types were minimally associated with SI/SB or IPST constructs; hopelessness was not associated. Overall, negative interpersonal beliefs and social cognitive biases may explain how CT increases suicide risk in psychosis.